First record of Dendropsophus anataliasiasi (Bokermann, 1972) (Anura, Hylidae) for the state of Pará, Brazil - Rachid, Lucas S. F.; Coelho, Gabriel N. C.; Carvalho, Augusto N.; Recoder, Renato; Farhat, Carolina; Rodrigues, Miguel T.; Moraes, Leandro J. C. L. (Herpetologia Brasileira, 2026)
This study reports the first record of Dendropsophus anataliasiae from the state of Pará, Brazil, in the municipality of Santana do Araguaia. This finding expands the known geographic distribution of the species, previously recorded in Cerrado areas approximately 229 km northwest of the type locality. The identification of the collected specimens was confirmed through morphological and genetic analyses. Morphologically, the individuals exhibited the diagnostic characters of the species, such as dorsal stripes, with slight variation in head measurements. DNA analyses corroborated the taxonomic identity, grouping the specimens with previously known sequences of the species. This record represents the 196th amphibian species documented for the state of Pará.